DEVELOPMENT OF ANIMATED VIDEO LEARNING MEDIA ASSISTED BY CANVA APPLICATION IN IPAS SUBJECTS ON ENERGY AND ITS CHANGES IN GRADE V ELEMENTARY SCHOOL - Novita, Widya; Ana Novitasari (Jurnal Tunas Pendidikan, 2024)
This research aims to develop animated video learning media assisted by the Canva application in the science and science subject of energy and its changes in class V elementary school. This research is motivated by a lack of innovation in the use of learning media which causes students to feel bored and less interested in learning. It is hoped that the learning media developed can increase students' interest in learning and make it easier for teachers to deliver the material. The research method used is the ADDIE development model which consists of five stages, namely analysis, design, development, implementation and evaluation. The results of the research show that the animated video learning media assisted by the Canva application has a high level of validity, practicality and effectiveness in science learning. This media can also attract students' attention, make it easier for them to understand the material, and improve student learning outcomes. This research concludes that animated video learning media assisted by the Canva application is effectively used as a tool in science and science learning in class V of elementary schools.